Hematological effects of the maleimide derivative during the activation of erythropoiesis induced by cobalt chloride - Byelinska, I.V.; Dzerzhynsky, M.E.; Rybalchenko, T.V.; Lynchak, O.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The effect of the protein kinase inhibitor maleimide derivative (MI-1, 1-(4-Cl-benzyl)-3-Cl-4-(CF3-pheny lamino)-1Hpyrrole-2,5-dione) with antitumor activity on the condition of blood cells during the activation of erythropoiesis induced by cobalt chloride has been studied. It is shown that MI-1 in a dose of 5 mg/kg (1/100 LD50) activates erythropoiesis, which is confirmed by an increase in the number of red blood cells, hematocrit, and the hemoglobin concentration in blood. With the combined action of MI-1 and CoCl2, the erythropoiesis stimulation is enhanced. MI-1 does not change the number of platelets in blood, but it slightly reduces the number of leukocytes due to neutrophilic granulocytes, monocytes, and lymphocytes, which testifies to the suppression of leukopoiesis. Thus, the stimulating effect of MI-1 on erythropoiesis and the low hematotoxicity of this compound indicate its superiority in comparison with traditional antitumor agents.